The Deconstruction Method in Contemporary Russian ‘new drama’ - Колбасин, Вадим Н. (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
Contemporary Russian ‘new drama’ is a controversy with a range of traditions in art, an attempt to protest against the established aesthetic forms which express the main line of modern theatre and drama. There is an idea of the relationship between literature and reality in the ‘new drama’ when the penetration into reality expresses a literary text de-aestheticization process. We determine the method of the Russian ‘new drama’ as deconstruction, which consists in the fact that the principle of authenticity in cooperation with the reality and its fixation are declared in contemporary ‘new drama’. First of all it is manifested in the choice of ‘material’ for the plays. Deconstruction appears with respect to the traditional ‘cultural’ drama topics. The taboo of physiological presentation is removed, violence becomes the basis of dramatic experience, and antiaesthetizm – the principle of its implementation. In the atmosphere of the ‘bottom of life’ every dramatic situation takes place. The antiheroes become heroes of the ‘new drama’. The character which is the most important category for drama is subject to deconstruction. The technique Verbatim (‘literally’), which is the basis of the documentary drama method, does not imply the well-defined author’s nature. The playwright is just a developer of issues and a ‘recording’ person. Religious, literary and historical myths undergo destruction. Finally, the deconstruction method influences poetics and the ‘new drama’ structure. The drama genre specificity is finally destroyed, there is even no attempt to identify the play genre. Thus, the multileveled deconstruction method becomes a determining factor for the ‘new drama’. This trend of simplification, fundamental principles de-aestheticization is not only in the drama but in the traditional relationship between art and reality.